National Esophageal Atresia Register - Sfeir, Rony; Michaud, Laurent; Sharma, Duyti; Richard, Florence; Gottrand, Frédéric (European Journal of Pediatric Surgery, 2015)
National Esophageal Atresia was created in 2008 by the National Reference Center for Esophageal Congenital Abnormalities created in 2006. Primary goal was estimation of live birth prevalence in France. A national network of surgeons and pediatricians was initiated and entire teams dealing with esophageal atresia accepted to participate in an exhaustive national register. A questionnaire was validated by a national committee and data were centralized in our center. Scientific exploitation showed that such database is useful for health authorities as for medical professionals. Live birth prevalence in France is at 1.9/10,000 births. Prenatal diagnosis is more common but its effect on prevalence is not yet fully understood. Associated congenital abnormalities are frequent and major malformations with termination of pregnancy can influence prevalence.
Keywords: esophageal atresia; register; live birth prevalence